VD_FINDINFO Jug / 2016 / 455 vom 30. Juli 2015 - VD Tribunal cantonal (2015)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, ADMISSION DE LA DEMANDE | 6 par. 1 CEDH, 30 al. 1 Cst., 56 CPP (CH), 58 CPP (CH), 59 CPP (CH)